2009
DOI: 10.1073/pnas.0900964106
|View full text |Cite
|
Sign up to set email alerts
|

Formation of harmful algal blooms cannot be explained by allelopathic interactions

Abstract: Many planktonic microalgae produce a range of toxins and may form harmful algal blooms. One hypothesis is that some toxins are allelopathic, suppressing the growth of competitors, and it has been suggested that allelopathy may be one important mechanism causing algal blooms. In a metaanalysis of recent experimental work, we looked for evidence that allelopathy may explain the initiation of algal blooms. With few exceptions, allelopathic effects were only significant at very high cell densities typical of bloom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 40 publications
3
104
1
1
Order By: Relevance
“…Algal blooms occur when algal growth exceeds zooplankton grazing. Thus, harmful algal blooms are thought to be facilitated by reduced grazing due to the algae producing toxic substances (Jonsson et al, 2009) that, in turn, are believed mainly to function as grazer deterrents. Reported grazer responses to harmful algae are diverse.…”
Section: Introductionmentioning
confidence: 99%
“…Algal blooms occur when algal growth exceeds zooplankton grazing. Thus, harmful algal blooms are thought to be facilitated by reduced grazing due to the algae producing toxic substances (Jonsson et al, 2009) that, in turn, are believed mainly to function as grazer deterrents. Reported grazer responses to harmful algae are diverse.…”
Section: Introductionmentioning
confidence: 99%
“…Sole et al [36] modified the allelopathic interaction term and proved that the role of allelopathy appears to be important only for high concentrations of the toxic algae. Recently, using simple models, Jonsson et al [19] supported the previous observation and confirmed that allelopathic (hereafter called a toxin) effect does not play any role to the initiation of algal blooms.…”
Section: Introductionmentioning
confidence: 66%
“…We have allocated a cost for producing toxic chemicals and toxin concentrations by separate equations. We have assumed that allelopathic effects become significantly important when the amount of toxin present in the system becomes very high (it has been reported by Sole et al [36]; Jonsson [19]). For numerical simulations, parameter values are taken from various literature sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smayda, 1997;Cembella, 2003;Tillmann, 2004;Jonsson et al, 2009), particularly for known toxigenic species. Among Alexandrium species, interspecific competition and antipredation defense mechanisms are most frequently invoked.…”
Section: Lytic Activitymentioning
confidence: 99%